Caracterização dos processos eletroquímicos em filmes automontados de poli(o-metoxianilina) e poli(ácido-3-tiofeno acético) - Strixino, Francisco Trivinho (Universidade Federal de São Carlos, 2003)
In this work, the electrochemical characterization of a self-assembled film containing two conductive polymers, poly(o-methoxyanilina)(POMA) and poly(3- thiophene acetic acid)(PTAA), is presented. The technique that allows to obtain these films is known as layer-by-layer (LBL) deposition. It consists in a spontaneous adsorption of species with opposite charges. The technique used for the electrochemical characterization was cyclic voltammetry coupled with mass variation using an electrochemical quartz crystal microbalance (EQCM), which allows the characterization of the LBL film mass/charge transport during the redox process. Electroacoustic impedance experiments of the LBL films with different number of bilayers show that the viscoelastic and mechanic tension properties do not change significantly in the potential range studied. Therefore, allowing the use of the Sauerbrey equation for converting the frequency values in mass values. The charge compensation mechanism was determined using the species flux (ions+solvent molecules) compared with POMA those casting films. The POMA-PTAA LBL film presents a charge compensation mechanism due to simultaneous intercalation of cations and anions. This behavior suggests the existence of a pseudo-self-doping mechanism related to carboxilic lateral groups interactions through the alternating layers structure of POMA-PTAA. The charge in the deprotonated carboxilic groups neutralize the charge generation of the imina groups present in the POMA backbone, which gives a decrease of the total mass change of the film. In this sense, the LBL technique could be an alternative method to prepare conducting polymer films modifying their electrochemistry properties.
Keywords: Físico química; Filmes automontados; Polímeros condutores; Layer-by-layer (LBL); Microbalança de cristal de quartzo; CIENCIAS EXATAS E DA TERRA::QUIMICA